E-Banking: Opportunities and Challenges from Customer’s Perspective - Aazib Afraz T N; Geetha R (Qubahan Academic Journal)
Opportunities and Challenges of E-Banking were empirically discussed. A researcher conducted a field investigation to collect the responses from the target audience. In the Technology Era, E-Banking has started to dominate the entire world. The presence of E-Banking can be seen till the tail end of small vicinities. Villagers also use it as it stops them from visiting bank branches. This increases trust as banks use high-end software for their banking system. The study was conducted in different parts of Chennai City. 210 customers were met in different parts of Chennai City. The places of research investigation covered by the researcher are shopping malls, Banks, Colleges, Universities, Business Outlets, and Residential Areas. Furthermore, the researcher used snowball sampling in the research as he collected the references of friends, family members, and colleagues. Descriptive Research Design was used by the researcher.